Implementing pop-up book-assisted STAD cooperative learning model to improve students’ descriptive writing skills - Juliana; Darinda Sofia Tanjung; Charles Andre F. Nieves; Dinesh Elango (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2025)
This paper documents the implementation of the STAD cooperative learning model assisted by pop-up book media to improve the descriptive writing skills of students in class VC UPT SDN 064025 Medan. This study is a classroom action research, which describes the process and results of actions taken in a classroom to improve results and quality of the learning process. The research subjects were students in class VC at UPT SDN Medan in the academic year 2024/2025. There were 25 students in class VC, consisting of 13 female and 12 male students. The research results indicate that implementing the STAD Cooperative Learning Model assisted by Pop-Up Books can improve descriptive writing skills, as evidenced by an increase in the learning completion rate from 64% in cycle I to 84% in cycle II. This shows that the STAD Cooperative Learning Model assisted by Pop-Up Books is suitable for improving elementary school students' descriptive writing skills.